RADIAL WRIST PAIN: A NARRATIVE REVIEW OF CONSERVATIVE AND SURGICAL TREATMENT STRATEGIES - Mateusz Kałwik; Piotr Komasara; Paweł Mikołajczak; Tomasz Szwarc; Mateusz Michalak; Hubert Bochenek; Michał Bzoma; Julia Nowakowska; Iga Klepacz; Milena Krawczyk (International Journal of Innovative Technologies in Social Science, 2025)
Radial wrist pain is a prevalent musculoskeletal complaint with a complex etiology involving soft tissue injury, degenerative changes, and fractures, particularly of the distal radius. This narrative review evaluates the efficacy, risks, and indications for conservative and surgical interventions by synthesizing data from over 12 clinical and systematic studies published between 2010 and 2024. Conservative treatment encompassing immobilization, NSAIDs, and physical therapy demonstrates substantial benefits in mild and non-displaced injuries, especially among elderly and pediatric patients. Surgical interventions, including arthroscopy, ligament reconstruction, and partial trapeziectomy, have shown improved outcomes in chronic, traumatic, or refractory cases. Specific advantages of minimally invasive techniques, such as 3A TFCC repair and percutaneous fixation, are highlighted. Treatment plans must consider age, functional demand, cost-effectiveness, and patient-specific pathology. The findings support a personalized and staged treatment approach for optimal recovery. Additionally, arthroscopic advancements have enabled more precise ligament reconstructions with less postoperative stiffness. Surgical techniques continue to evolve with the adoption of augmented reality guidance and intraoperative 3D imaging, promising even better alignment and outcomes.